Brecht and Political Theatre : the Mother on Stage. - Bradley, Laura (Oxford modern languages and literature monographs., 2006)
This study focuses on The Mother, Bertolt Brecht's most overtly political play and the only play which he staged in the Weimar Republic. Through detailed analysis of archival material, Bradley explores how Brecht's theatre practice developed and how it has subsequently been received and challenged by other directors, in and beyond Germany. - ;This production history of The Mother provides substantial new insights into Bertolt Brecht's theatre and drama, his impact on political theatre, and the relationship between text, performance, and politico-cultural context. As the only play which Brecht.